Safe and Efficacious Use of 1-Month Triple Therapy in Patients with Atrial Fibrillation and High Bleeding Risk Undergoing PCI - Sambola, Antonia (2019)
Background: The impact of short or prolonged use of triple therapy (TT) on outcomes in patients with atrial fibrillation (AF) and high risk of bleeding undergoing percutaneous coronary intervention (PCI) is unclear. We compared clinical outcomes according to the duration of TT in patients with AF and HAS-BLED ≥ 3 at 1 year of follow-up. Methods: A prospective observational cohort enrolled 735 patients with AF between 2010 and 2015. Of these, 521 (70.9%) had HAS-BLED ≥ 3 and 380 (72.9%) were discharged on TT. TT was prescribed for 1 month in 233 patients (61.3%). The primary endpoint was the incidence of Bleeding Academic Research Consortium (BARC ≥ 3). The secondary endpoint was the occurrence of ischemic events (cardiac death, MI, stroke, or stent thrombosis). Results: Patients on 1-month TT had a higher median HAS-BLED. Intracraneal hemorrhage was twofold more frequently in patients on > 1-month TT but without statistical significance (0.9% vs 2.1%, p = 0.20). Rates of the primary endpoint (bleeding BARC ≥ 3) were 8.2% vs 10.9% and did not differ between groups, while secondary endpoint did not occur more frequently in the 1-month TT group compared with the > 1-month TT group (26.6% vs 23.1%). In adjusted multivariate analyses, patients receiving 1-month TT had a similar risk of the primary endpoint compared to those with > 1-month TT (HR 1.47; 95% CI 0.48–4.47, p = 0.50). No difference was found in the secondary ischemic endpoint (HR 1.24; 95% CI 0.77–2.00, p = 0.38).